Diet and risk of breast, endometrial and ovarian cancer: UK Women's Cohort Study. Issue 5 (11th December 2018) - Dunneram, Yashvee; Greenwood, Darren C.; Cade, Janet E.
Abstract: This study aimed to investigate the association between diet and the risk of breast, endometrial and ovarian cancer in the UK Women's Cohort Study. A total of 35 372 women aged 35–69 years were enrolled between 1995 and 1998 and completed a validated 217-item FFQ. The individual foods were collapsed into sixty-four main food groups and compared using Cox proportional models, adjusting for potential confounders. Hazard ratio (HR) estimates are presented per portion increase in food items. After approximately 18 years of follow-up, there were 1822, 294 and 285 cases of breast, endometrial and ovarian cancer, respectively. A high consumption of processed meat and total meat was associated with an increased risk of breast and endometrial cancer. High intake of tomatoes (HR 0·87, 99 % CI 0·75, 1·00) and dried fruits (HR 0·60, 99 % CI 0·37, 0·97) was associated with a reduced risk of breast and endometrial cancer, respectively. Mushroom intake was associated with a higher risk of ovarian cancer (HR 1·57, 99 % CI 1·09, 2·26). Subgroup analysis by pre- or postmenopausal cancer further demonstrated an association between processed meat intake and both postmenopausal breast cancer and endometrial cancer. Intake of dried fruits was associated with a reduced risk of postmenopausal endometrial cancer (HR 0·55, 99 % CI 0·31, 0·98). Our findings suggest that while some foods may trigger the risk of these cancers, some foods may also be protective; supporting the call for further randomised controlled trials of dietary interventions to reduce the risk of cancer among pre- and postmenopausal women.